Журналістсько-публіцистична діяльність Дениса Квітковського в контексті розвитку українського національного руху на Буковині в 30-х рр. ХХ ст. - Попович, Юлія Олександрівна (Інститут журналістики КНУ імені Тараса Шевченка, 2013)
The article deals with development of the Ukrainian nationalistіс press in Bukovina region in the 30-s of the XX centure. The attention is drawn to social and political conditions under which national journalism was developed in the interwar period. In particular, a special attention was paid to the weekly “Samostiynist” and to the activity of its editor D.Kvitkovskjy’s as a journalist and a publicist.
Journalistic activities of Denys Kvitkovs'kyj in the context of development of the Ukrainian national movement in Bukovina region in the 30-s of the XX centure
Keywords: edition, magazine, nationalistic press, periodicals, weekly, interwar period; видання, часопис, націоналістична преса, періодика, тижневик, міжвоєнний період